2018
DOI: 10.1523/jneurosci.3113-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

Fear Memory Recall Potentiates Opiate Reward Sensitivity through Dissociable Dopamine D1 versus D4 Receptor-Dependent Memory Mechanisms in the Prefrontal Cortex

Abstract: Disturbances in prefrontal cortical (PFC) dopamine (DA) transmission are well established features of psychiatric disorders involving pathological memory processing, such as post-traumatic stress disorder and opioid addiction. Transmission through PFC DA D4 receptors (D4Rs) has been shown to potentiate the emotional salience of normally nonsalient emotional memories, whereas transmission through PFC DA D1 receptors (D1Rs) has been demonstrated to selectively block recall of reward- or aversion-related associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 55 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Moreover, it has been found that noradrenergic overstimulation in individuals with PTSD may also increase their predisposition to illicit drug use for self-medication, especially for substances with sedative properties, such as alcohol, opioids, and benzodiazepines[54]. It has been recently demonstrated in a rodent model[55] that abnormal dopamine signals in the prefrontal cortex may underlie the ability of traumatic memories to predispose individuals to addiction by increasing their sensitivity to the rewarding effects of drugs such as opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been found that noradrenergic overstimulation in individuals with PTSD may also increase their predisposition to illicit drug use for self-medication, especially for substances with sedative properties, such as alcohol, opioids, and benzodiazepines[54]. It has been recently demonstrated in a rodent model[55] that abnormal dopamine signals in the prefrontal cortex may underlie the ability of traumatic memories to predispose individuals to addiction by increasing their sensitivity to the rewarding effects of drugs such as opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence show that dopamine D1 receptors expressed in the NAc, the PFC, hippocampus and the amygdala play a critical role in fear learning and fear extinction (Abraham et al, 2016a;2016b;Borowski and Kokkinidis, 1998;Fadok et al, 2009;Hikind and Maroun, 2008;J. J. Li et al, 2018;Ng et al, 2018).…”
Section: Obesogenic Diet Leads To Abnormal Maturation Of the Neural Amentioning
confidence: 99%
“…D1 and D2 antagonists block the acquisition of fear memories 3–7 whilst the administration of D1 or D2 agonists increase fear expression 8,9 . Blockade of D3 receptors has, surprisingly, shown to enhance fear acquisition 10 , whilst D4 activation potentiates acquisition 11 . In humans, the effects of a dopamine reuptake blocker (Ritalin) or a dopamine precursor (L-Dopa) have only been investigated with respect to fear extinction and spontaneous recovery 12,13 , but not fear acquisition.…”
Section: Introductionmentioning
confidence: 99%